Three-Phase Partitioning of Peroxidase from Flowers of Citrus sinensis for Use in Diagnostic Kit - Uckaya, Fatih; Demir, Nazan (Asian Journal of Chemistry, 2017)
This study presents purifying of peroxidase enzyme from flowers of Citrus sinensis that used in glucose diagnostic kits by three-phase partitioning technique. Three-phase partitioning technique was chosen due to its simplicity and economical feasibility. An appropriate salt and organic solvent were used to separate the enzyme from aqueous solutions in the system. The homogenate:t-butanol ratio and the concentration of ammonium sulphate were determined as 1:1.5 and 40 %, respectively. Optimum pH (9), optimum temperature (40 °C), KM (9.84 mM) and Vmax (7.69 U/mL.min) values of the enzyme were calculated using the 4-aminoantipyrine-phenol system. The purity and activity recovery of the enzyme were determined as 9.02-fold and 677.51 %, respectively. The molecular weight (45 kDa) of the enzyme was estimated using SDS-PAGE. The purified enzyme was used in the glucose diagnostic kit. As a result, peroxidase was purified successfully by three-phase partitioning and worked well with the glucose diagnostic kit.